The distinct effects of metformin and imeglimin on high glucose-induced alterations in metabolic function and reactive oxygen species production in mouse Schwann cells are modulated by pemafibrate and/or fatty acid-binding proteins. - Ohguro, Hiroshi; Higashide, Megumi; Nishikiori, Nami; Ogawa, Toshifumi; Furuhashi, Masato; Sato, Tatsuya; Watanabe, Megumi (Frontiers in Cellular Neuroscience, 2025)
BackgroundImeglimin (Ime), the first in a novel class of antidiabetic agents, has potential therapeutic effects on diabetic peripheral neuropathy (DPN). This study aimed to evaluate and compare the effects on cellular metabolic function and reactive oxygen species (ROS) levels in high glucose-treated mouse Schwann cells (SCs), an in vitro DPN model, with those of metformin (Met), a conventional antidiabetic agent known for its beneficial effects on DPN. The roles of PPARα and fatty acid-binding proteins 5 and 7 (FABP5 and FABP7), both of which have been implicated in the pathogenesis of DPN, were also investigated.MethodsSchwann cells were treated with high glucose, Ime, Met, a selective PPARα agonist pemafibrate (Pema), or a FABP5/FABP7 inhibitor (MF6). Cell viability assays, extracellular flux analysis, and ROS production assays were performed.ResultsNo significant changes in cell viability were observed with any treatment. High glucose exposure increased glycolytic reserve compared to normal glucose conditions. Ime increased mitochondrial respiratory functions, whereas Met suppressed mitochondrial respiration and enhanced glycolytic functions, with these effects being more evident under normal glucose conditions. Pema significantly increased basal glycolysis under high glucose conditions, while MF6 had no appreciable effect. Both Ime and Met reduced ROS production in high glucose-treated SCs, with Ime exhibiting a more potent effect. However, the ROS-reducing effects of Ime and Met were abolished by Pema or MF6.ConclusionImeglimin exerted beneficial biological effects by enhancing the energetic state and reducing ROS production without inducing metabolic quiescence in high glucose-treated SCs. These findings suggest that Ime has therapeutic potential for DPN, although its effects may be modulated by intracellular lipid metabolism.